Research on the value orientations of students using information and communication technologies - Yivzhenko, Yurii; Vorontsova, Emilia; Kreminskyi, Borys; Savenko, Oleksandr; Illarionov, Valerii (International Journal of Innovative Research and Scientific Studies, 2023)
The current study is an attempt to compare online and offline results of research on students’ value orientations. The main scientific methods and approaches used in the current research are comparative analysis, online and offline comparison and statistical rank correlation. We defined the questionnaire’s content, formed its text and chose homogeneous representative groups. Results obtained both with classical (paper) technology and with information and communication technologies (ICT) are compared. The terminal and instrumental sets of values proposed by Milton Rokeach are compared. Based on the processed data, we draw conclusion about the reliability (validity) of online survey results. ICT is very helpful in conducting scientific research faster with fewer professionals involved but its time-consuming and requires numerous activities. Recommendations are given on the feasibility of using ICT in modern methods of sociological research. Work on the creation of modern research platforms, programs and algorithms that would ensure obtaining valid and informative results is prominent among the aspects of further scientific research.